Screening for social determinants of health among populations at risk for MASLD: a scoping review - Kim, Rebecca G.; Ballantyne, April; Conroy, Molly B.; Price, Jennifer C.; Inadomi, John M. (Frontiers in Public Health, 2024)
Background: Social determinants of health (SDoH) have been associated with disparate outcomes among those with metabolic dysfuncUon-associated steatoUc liver disease (MASLD) and its risk factors. To address SDoH among this populaUon, real-Ume SDoH screening in clinical sefngs is required, yet opUmal screening methods are unclear. We performed a scoping review to describe the current literature on SDoH screening conducted in the clinical sefng among individuals with MASLD and MASLD risk factors. Methods: Through a systemaUc literature search of MEDLINE, Embase, and CINAHL Complete databases through 7/2023, we idenUfied studies with clinic-based SDoH screening among individuals with or at risk for MASLD that reported perUnent clinical outcomes including change in MASLD risk factors like diabetes and hypertension. Results: Ten studies (8 manuscripts, 2 abstracts) met inclusion criteria involving 148,151 paUents: 89,408 with diabetes and 25,539 with hypertension. Screening was primarily completed in primary care clinics, and a variety of screening tools were used. The most commonly collected SDoH were financial stability, healthcare access, food insecurity and transportaUon. AssociaUons between clinical outcomes and SDoH varied; overall, higher SDoH burden was associated with poorer outcomes including elevated blood pressure and hemoglobin A1c. Conclusion: Despite numerous epidemiologic studies showing associaUons between clinical outcomes and SDoH, and guidelines recommending SDoH screening, few studies describe in-clinic SDoH screening among individuals with MASLD risk factors and none among paUents with MASLD. Future research should prioriUze real-Ume, comprehensive assessments of SDoH, parUcularly among paUents at risk for and with MASLD, to miUgate disease progression and reduce MASLD health dispariUes.